The Roles and Value of Citizen Science: Perceptions of Professional Educators Enrolled on a Postgraduate Course. (1st December 2021) - Aristeidou, Maria; Ferguson, Rebecca; Perryman, Leigh-Anne; Tegama, Natalie
Recent findings regarding learning in Citizen Science (CS) have led to an increase in CS project popularity in formal education classrooms. However, there has been little discussion of educators' initial views on CS. This study examined the perceptions of professional educators enrolled on a postgraduate course in relation to expertise and data quality in CS and to how CS can enhance learning. Collected data comprised comments on the FutureLearn platform made by 164 educators, over two years, after they became involved in CS activities while studying. Findings showed that, overall, educators recognise the power of CS for learning, but are sceptical about the role of experts and the quality of data gathered in this way. Further results highlighted the different motivations educators have for participating in CS (compared with other volunteers) and their need to frame learning that takes place through CS using learning theories and models. The findings of this study have considerable implications for research into designing training activities that introduce educators to CS in classroom settings and support their role as intermediaries of CS.